Recent advances in active, smart and edible packaging applications to enhance post-harvest quality and shelf-life of fruits - Chan, Wei Chuen; Kaseke, Tafadzwa; Chew, Sook Chin; Neo, Yun Ping; Nyam, Kar Lin (Frontiers in Food Science and Technology, 2025)
Post-harvest fruit losses result in significant waste problem due to the decline in quality by physiological metabolism and unfavorable environmental conditions. To extend shelf life and mitigate waste and environmental impacts, investigations on innovative fruit packaging technologies such as active, edible, biodegradable, and smart packaging are warranted. Active packaging enhances fruit preservation by ethylene scavengers, controlling fungal growth, regulating moisture, and providing antioxidants through bioactive compounds. A growing trend involves edible and biodegradable packaging made from natural polymers (polysaccharides, proteins, and lipids), which prevents physical, mechanical, and microbiological damage to fruits while also serving as a medium for additives like antimicrobials and antioxidants, thus improving freshness and quality. In addition, smart packaging utilizes biosensors, pH indicators, and gas indicators for live monitoring throughout the supply chain and can be united with other packaging technologies to enhance functionality. Current developments concern on the green and hybrid packaging, particularly to unite biodegradable packaging with active and smart packaging to deliver synergistic functionalities. This can preserve the fruits quality while offering active properties or live monitoring while supporting environmental sustainability. This review provides insights on the current advances and potential future development in innovative active, edible, biodegradable, and smart packaging technologies, while also addressing the current challenges associated with these packaging.